2020
DOI: 10.1186/s13568-020-01067-7
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and maintenance of NESTIN expression in umbilical cord-MSC using a novel culture medium

Abstract: Mesenchymal stem cells (MSC) are a popular candidate in cellular therapy for many diseases. MSCs are well known by their feature of self-renewal and their differentiation potential. NESTIN is a cytoskeletal protein expressed in MSC that functions directly in cell proliferation and differentiation. Here, we demonstrated that adding UltraGRO, a medium supplement, could maintain and partially recover the expression of NESTIN in human umbilical cord derived MSCs (UC-MSCs). Furthermore, the UC-MSCs cultured with Ul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Nestin is a class VI intermediate filament protein, which is usually expressed by stem-like cells, including neural stem or progenitor cells (Bernal and Arranz, 2018), tumor stem cells (Neradil and Veselska, 2015) and MSCs of various tissues (Yin et al, 2016;Lu et al, 2019;Liao et al, 2020). Nestin functions are associated with the self-renewal, proliferation, differentiation and migration of stem cells, and previous research reports that Nestin expression gradually decreases with increasing MSCs passage (Liu et al, 2020). In the current study we found higher Nestin expression in the hPL-UCMSCs group than FBS-UCMSCs at P4, which may be the cause of group differences in cell proliferation, senescence, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin is a class VI intermediate filament protein, which is usually expressed by stem-like cells, including neural stem or progenitor cells (Bernal and Arranz, 2018), tumor stem cells (Neradil and Veselska, 2015) and MSCs of various tissues (Yin et al, 2016;Lu et al, 2019;Liao et al, 2020). Nestin functions are associated with the self-renewal, proliferation, differentiation and migration of stem cells, and previous research reports that Nestin expression gradually decreases with increasing MSCs passage (Liu et al, 2020). In the current study we found higher Nestin expression in the hPL-UCMSCs group than FBS-UCMSCs at P4, which may be the cause of group differences in cell proliferation, senescence, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of MSCs from BM, UC, and UC blood found all expressed similar markers, yet only UC-MSCs and UC blood MSCs did not express HLA-DR associated with transplant rejection, making them more similar to AD-MSCs [ 99 ]. Although, UC-MSCs express nestin early after isolation, their expression declines with passage [ 100 , 101 ]. This reduction in nestin expression correlated with reduced anti-inflammatory capacity later in passage [ 101 ].…”
Section: Umbilical-cord-derived Mesenchymal Stromal Cells (Uc-mscs)mentioning
confidence: 99%
“…Although, UC-MSCs express nestin early after isolation, their expression declines with passage [ 100 , 101 ]. This reduction in nestin expression correlated with reduced anti-inflammatory capacity later in passage [ 101 ]. In addition, cell surface marker expression is thought to change in passage and may indicate epigenetic phenomena associated with cell culture [ 102 ].…”
Section: Umbilical-cord-derived Mesenchymal Stromal Cells (Uc-mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Table 1 , different culture media without foetal bovine serum (FBS) have been used by Kang JY et al [ 58 ], Wu X et al [ 59 ], and Liu Y et al [ 60 ] during the ex vivo expansion of the MSCs. These authors observed enhanced immunomodulatory effects of MSCs in in vivo models of IBD, thus reducing the risk of xenoimmunization and zoonotic transmission.…”
Section: Strategies To Boost Msc-based Therapy In Ibdmentioning
confidence: 99%